Animaux domestiques dans la littérature narrative française au Moyen Âge - Jens N. Faaborg (Museum Tusculanum Press, 2006)
After a presentation of horses including a long line of proper names and of the remaining mammals and birds on the farm in the Middle Ages, follows an examination of the lives of these domestic animals and their exploitation and an enumeration of their appearance within ideas, language and fantasy. Furthermore, the book contains various tables and an index as well as a bibliography.